Formative Assessment Practiced By EFL Lecturers in STAIN Majene - Delfina Gemely; Baso Jabu; La Sunra (Pascasarjana Universitas Negeri Makassar, 2022)
This research aimed to find out (1) how do EFL lecturers perceive formative assessment? (2) How do EFL lecturers practice formative assessment? This research employed a qualitative research design based on a case study approach involving three EFL lecturers in STAIN Majene. Data collection methods include interviews, classroom observations, and documentation. The result of the study showed that (1) the EFL lecturers perceived formative assessment practice mainly as a process of giving feedback for the student's improvement and for adjusting their instruction. and (2) learning targets, monitoring, feedback, self-assessment, and peer assessment assisted the EFL lecturers and students in achieving their learning objectives. The present study concluded that EFL lecturers perceived that the experience of implementing formative assessment has shaped their perceptions of EFL lecturers. The EFL lecturers got various and different experiences in practicing formative assessment.